Prolonged evolution of virus-specific memory T cell immunity post severe avian influenza A (H7N9) virus infection - Zhao, M; Chen, J; Tan, S; Dong, T; Jiang, H; Zheng, J; Quan, C; Liao, Q; Zhang, H; Wang, X; Wang, Q; Bi, Y; et al. (American Society of Microbiology, 2018)
Since 2013, influenza A/H7N9 has emerged as the commonest avian influenza subtype causing human infection, and is associated with a high fatality risk. However, the characteristics of immune memory in patients who have recovered from H7N9 infection are not well understood. We assembled a cohort of forty-five H7N9 survivors followed for up to 15 months after infection. Humoral and cellular immune responses were analyzed in sequential samples obtained at 1.5-4 months, 6-8 months and 12-15 months post-infection. H7N9-specific antibody concentrations declined over time, and protective antibodies persisted longer in severely ill patients admitted to ICU and patients presenting with ARDS than that in patients with mild disease. Frequencies of virus-specific IFN-γ secreting T cells were lower in critically ill patients requiring ventilation than those in patients without ventilation within four months after infection. The percentages of H7N9-specific IFN-γ secreting T cells tended to increase over time in patients ≥60 years or critically ill patients requiring ventilation. Elevated levels of antigen-specific CD8+ T cells expressing lung-homing marker CD49a were observed at 6-8 months after H7N9 infection compared to samples obtained at 1.5-4 months. Our findings indicate the prolonged reconstruction and evolution of virus-specific T cell immunity in older or critically ill patients, and provide implications for T-cell directed immunization strategies.IMPORTANCE Avian influenza A H7N9 remains a major threat to public health. However, no previous studies have determined the characteristics and dynamics of virus specific T cell immune memory in patients who have recovered from H7N9 infection. Our findings showed that establishment of H7N9-specific T cell memory after H7N9 infection was prolonged in older and severely affected patients. Severely ill patients mounted lower T cell responses in the first 4 months after infection, while T cell responses tended to increase over time in older and severely ill patients. Higher levels of antigen-specific CD8+ T cells expressing the lung-homing marker CD49a were detected at 6-8 months after infection. Our results indicated a long term impact of H7N9 infection on virus-specific memory T cells. These findings advance our understanding of the dynamics of virus-specific memory T cell immunity after H7N9 infection, relevant to the development of T cell based universal influenza vaccines.